Colonic Malakoplakia in a Liver Transplant Recipient - Peter TW Kim; Jennifer E Davis; Siegfried R Erb; Eric M Yoshida; Urs P Steinbrecher (Canadian Journal of Gastroenterology)
Malakoplakia is a rare inflammatory condition seen in transplant patients. There are two previously reported cases of malakoplakia involving the gastrointestinal tract in liver transplant patients. The present paper reports a case of colonic malakoplakia in a 58-year-old woman, a liver transplant recipient who was receiving immunosuppressive drugs. She presented with chronic diarrhea while on tacrolimus. There was no history of antecedent infection. Colonoscopy showed patchy mucosal edema, but no discrete yellow plaques or nodules. The diagnosis was made by colon biopsies, which showed chronic inflammation with many histiocytes containing Michaelis-Gutmann bodies. Although rare, malakoplakia is one of many potential causes of diarrhea in a transplant patient. The present case indicates that malakoplakia may be associated with chronic diarrhea, even if there are no macroscopic lesions seen during colonoscopy.